In Vivo Magic Angle Magnetic Resonance Imaging for Cell Tracking in Equine Low-Field MRI - Carolin Horstmeier; Annette B. Ahrberg; Dagmar Berner; Janina Burk; Claudia Gittel; Aline Hillmann; Julia Offhaus; Walter Brehm (Hindawi Limited, 2019)
The magic angle effect increases the MRI signal of healthy tendon tissue and could be used for more detailed evaluation of tendon structure. Furthermore, it could support the discrimination of hypointense artefacts induced by contrast agents such as superparamagnetic iron oxide used for cell tracking. However, magic angle MRI of the equine superficial digital flexor tendon has not been accomplished in vivo in standing low-field MRI so far. The aim of this in vivo study was to evaluate the practicability of this magic angle technique and its benefit for tracking superparamagnetic iron oxide-labelled multipotent mesenchymal stromal cells. Six horses with induced tendinopathy in their forelimb superficial digital flexor tendons were injected locally either with superparamagnetic iron oxide-labelled multipotent mesenchymal stromal cells or serum. MRI included standard and magic angle image series in T1- and T2∗-weighted sequences performed at regular intervals. Image analysis comprised blinded evaluation and quantitative assessment of signal-to-noise ratio. The magic angle technique enhanced the tendon signal-to-noise ratio (P<0.001). Hypointense artefacts were observable in the cell-injected superficial digital flexor tendons over 24 weeks and artefact signal-to-noise ratio differed significantly from tendon signal-to-noise ratio in the magic angle images (P<0.001). Magic angle imaging of the equine superficial digital flexor tendon is feasible in standing low-field MRI. The current data demonstrate that the technique improves discrimination of superparamagnetic iron oxide-induced artefacts from the surrounding tendon tissue.